Solid Particle Erosion Behavior of A Boiler Steel - Supreet singh, Manpreet kaur (International Journal of Advanced Science and Technology, 2020)
SAE-210 GrA1 steel is a well known candidate for fabricating boiler tubes in thermal power plants. Although these materials have adequate mechanical strength at elevated temperatures, they often lack resistance to corroding and eroding environments during longer durations of usage. Singlepromisingmode to avoid substratedeteriorationissue is the use of protective layred techniques for example coatings. Out of variousexterioramendmentmodus operandi, spraying using thermalgenerated ascomparativelyspeedilybecause oftrending advanced varnishlayers of coatings and step up in functionmachinery of coating. Authors in this current study have studied that development of High Velocity Oxy-Fuel (HV-OXY FUEL)sparying has expand fame in past years because of liability in situ submission and better-qualityglaze properties.In the present study, solid particle erosion behavior of a boiler steels namely ASTM-SAE210-Grade A1 has been investigated with and without the application of HV-OXY FUEL sprayed composite coatings. The selected 50% (NiCrSiBFeC) +50 %(Cr3C2byHV-OXY FUELtechnique was used at Grade A1steel, which include low percentage of carbon. The Microhardness, Coating Bond Strength and Coating Surface Roughness for base and coated steel was also compared in this study